GAMBARAN PELAKSANAAN PROGRAM PROMOSI K3 PADA PT PERTAMINA TRANS KONTINENTAL JAKARTA TAHUN 2018 - Irenia Tennovia Yulius; Siti Rahma H. Lubis (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2019)
Work accidents and occupational diseases can adversely affect both material and non- material to the company. Recorded by BPJS Ketenagakerjaan, 2016 there are still 101,367 cases of work accidents in Indonesia. In preventing it is necessary a form of prevention of work accident. One of the efforts to prevent accidents is by doing health and safety promotion in the company environment. Health and Safety promotion conducted by PT. Pertamina Trans Continental has various forms of programs. Information on Health and safety promotion conducted at the company is obtained through interview, observation, and document review. In the implementation of Health and safety promotion at PT. Pertamina Trans Continental in general is in accordance with existing theories and policies. However, in some cases still need to be considered and improved in the implementation and evaluation of every Health and safety promotion program. It is done either based on the existing theory and based on the policy used as a reference in every existing program. Suggestions for improvement of Health and safety promotion program is to evaluate the effectiveness of health and safety training which can be measured and documented, monitoring and evaluation of safety sign that already exist. As well as implementing punishment system, evaluation of effectiveness orientation familiarization, as well as making of Health and safety promotion procedure. Keywords: Health and safety promotion, PT. Pertamina Trans Kontinental